Why does 2-(2-aminoethylamino)ethanol have superior CO2 separation performance to monoethanolamine? A computational study. Issue 23 (7th June 2022) - Aso, Daiki; Orimoto, Yuuichi; Higashino, Makoto; Taniguchi, Ikuo; Aoki, Yuriko
Abstract : The high CO2 separation performance of 2-(2-aminoethylamino)ethanol can be theoretically explained by the high sorption ability of its primary amine and the high desorption ability of its secondary amine. Abstract : Our computational reaction analysis shows that 2-(2-aminoethylamino)ethanol (AEEA) has superior performance to monoethanolamine for CO2 separation, in terms of its ability to sorb CO2 by its primary amine and desorb CO2 by its secondary amine.